FORMULATION AND EVALUATION OF SUBMICRON EMULSION CONTAINING ENTRAPPED FLUOROQUINOLONE FOR OCULAR DELIVERY - Pandey, Durga; Jain, Deepti (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the present work was to develop and characterize the submicron emulsion bearing antimicrobial drug sparfloxacin for improvement of ocular activity by improved retention in eyes. The developed delivery system was results with prolonged drug release as compared to the conventional dosage form. Methods: SE prepared by high energy emulsification and sonication to obtain uniform globule size. Results: Average internal droplets size of the optimized formulation was 0.278±0.6 μm, pH of the optimized formulation was 6.9±0.6 (average of three determinations), and viscosity 2.9±0.5 cps suitable for ocular use. Entrapment of SF was 63±3.4%. Stable under accelerated and long-term at 4°C and 37°C. No major changes reported on pH and viscosity of optimized formulations. In vitro, drug release pattern showed sustain release of SF, a cumulative percent release of SF was found 87.8±1.7% within 24 h. Transmission electron microscopy showed spherical shape and size within 1 μm. Conclusion: Designed formulation can be a good candidate for ocular drug delivery for severe ocular infections where frequent dosing required for conditions such as endophthalmitis, corneal ulcer, and penetrating trauma.